Integrating Incompatible Nanozyme‐Catalyzed Reactions for Diabetic Wound Healing. Issue 10 (21st December 2022) - Li, Guangming; Liu, Hao; Yi, Jiadai; Pu, Fang; Ren, Jinsong; Qu, Xiaogang
Abstract: Multi‐nanozymes are widely applied in disease treatment, biosensing, and other fields. However, most current multi‐nanozyme systems exhibit only moderate activity since reaction microenvironments of different nanozyme are often distinct or even incompatible. Conventional assemble strategies are inapplicable for designing multi‐nanozymes consisting of incompatible nanozymes. Herein, a versatile fiber‐based compartmentalization strategy is developed to construct multi‐nanozyme system capable of simultaneously performing incompatible reactions. In this system, the incompatible nanozymes are spatially distributed in distinct compartmentalized fibers, where different microenvironments can be tailored by controlling the doping reagent, endowing each nanozymes with the preferential microenvironments to exhibit their highest activity. As a proof of concept, pH‐incompatible peroxidase‐like and catalase‐like catalytic reactions are tested to verify the feasibility of this strategy. By doping with benzoic acid in the desired location, the two pH‐incompatible nanozymes can work simultaneously without interference. Further, it is demonstrated that the oxygen supply and antimicrobial power of the integrated platform can be applied for accelerating diabetic wound healing. It is hoped that this work provides a way to integrate incompatible nanozyme and broadens the application potential of multi‐nanozymes. Abstract : In this work, incompatible nanozyme‐catalyzed reactions are successfully integrated via a fiber‐based compartmentalization strategy. Benefiting from compartmentalization, tailored reaction microenvironments are constructed for different nanozymes, allowing nanozyme‐catalyzed reactions to occur simultaneously and efficiently. This multi‐nanozyme cooperative system provides impressive therapeutic effects in accelerating diabetic wound healing by inhibiting bacterial colonization, reducing inflammation, and promoting epithelialization and angiogenesis.